Introductory editorial thematic issue: geochemistry of surface processes (III RAGSU) - Martinez, Daniel Emilio (2017)
Geochemistry, as a discipline linking geology and chemistry,was from the beginning focused on the study of thecomposition of rocks and their formation. The disciplinedeveloped the same way in Argentina and similarly in therest of Latin America. One of the papers included particularlyin this Thematic Issue is related to the history ofgeochemistry, which constituted a starting point andmoreover a reference for present day investigations.Geological materials, formed at high pressures andtemperatures, outcrop at the surface, forming the Earth?slandscape. Upon being exposed to low pressure and temperatureconditions, they interact with the atmosphere, thehydrosphere and the human race. Thus, minerals becomeunstable; chemical elements take ionic forms and are ableto move in water and air; new substances are created byman; and other natural products are strongly concentratedin some sites. The study of geochemical processes of theEarths surface, as a new area of geochemistry whereinterdisciplinary work is prevalent, is focused on chemicalreactions which attempt to attain a steady state and,moreover, on geological movements of materials whichalter that chemical equilibrium.